Ferdinand de Saussure: Structuralism and His Role in Modern Linguistics - Khoirul Zaman Al Umma (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
Structuralism emerged in the twentieth century with the publication of Course in General Linguistics, a work based on the lectures of Ferdinand de Saussure at the University of Geneva. Although the book was compiled and published posthumously by his students rather than written directly by Saussure himself, it is widely regarded as a landmark that revolutionized modern linguistic thought. Structural linguistics analyzes language by focusing on its internal structure rather than on its historical development. Saussure viewed language as an organized system of interrelated elements and distinguished between langue, the abstract system of language shared by a speech community, and parole, the individual act of speech or communication. The linguistic principles proposed by Saussure introduced a new methodological framework for language analysis that differed fundamentally from the historical-comparative approach that had dominated linguistic studies before the emergence of structuralism. This paper discusses the essential principles of Saussure's structuralist theory and examines its significant contribution to the development of modern linguistics.